Application of the pH-Responsive PCL/PEG-Nar Nanofiber Membrane in the Treatment of Osteoarthritis - Wang, Zetao; Zhong, Yanping; He, Si; Liang, Ruiming; Liao, Chuanan; Zheng, Li; Zhao, Jinmin (Frontiers in Bioengineering and Biotechnology, 2022)
Electrospinning technology is widely used in the field of drug delivery due to its advantages of convenience, high efficiency, and low cost. To investigate the therapeutic effect of Naringenin (Nar) on osteoarthritis (OA), the pH-responsive system of polycaprolactone/polyethylene glycol-Naringenin (PCL/PEG-Nar) nanofiber membrane was designed and used as drug delivery systems (DDS) in the treatment of OA. The PEG-Nar conjugate was constructed via ester linkage between mPEG-COOH and the carboxyl group of naringenin, and the PCL/PEG-Nar nanofiber membrane was prepared by electrospinning technology. When placed in the weak acid OA microenvironment, the PCL/PEG-Nar nanofiber membrane can be cleverly "turned on" to continuously release Nar with anti-inflammatory effect to alleviate the severity of OA. In this study, the construction and the application of the pH-responsive PCL/PEG-Nar nanofiber membrane drug delivery platform throws new light to OA treatment.